Phenotype and genotype of bovine viral diarrhoeavirus isolated in Peruvian cattle - Araínga R., Mariluz (2010)
The aim of this study was to determine the phenotype and genotype of Bovine Viral Diarrhoea Virus (BVDV) in Peruvian cattle. During the period 1998-2007, tissues of aborted foetus, blood, serum or plasma samples of bovine with acute infection or persistently infected from dairy herds of various locations in the country were collected and the BVDV antigen was detected by immnunofluorescence or capture ELISA tests, and positive samples were inoculated en BVDV free BT cells and cultured until third passage to determine the biotype. Both animal tissues and third passage of positive samples were tested by a Real Time Reverse Transcription-Polymerase Chain Reaction (RT-PCR) for genotyping the strains. Forty one BVDV strains were isolated in BT cells. Eighty five percent (35/41) of the isolates were non-cytopathic and 14.6% (6/41) cytophatic. Forty five and a half percent (25/55) and 74.5% (41/55) of the animal tissues and from the 3rd passage samples respectively, were positive to BVDV by Real Time RT-PCR test. All isolates belonged to BVDV-1 genotype. These results contribute to a better understanding of the epidemiology of the bovine viral diarrhoea disease in Peru and suggest that BVDV-2 is absent or has low prevalence in dairy herds.